Impact of body mass index on postoperative oxygenation impairment in patients with acute aortic syndrome - Zhang, Chiyuan; Bai, Hui; Zhang, Yanfeng; Deng, Zhengyu; Zhang, Lei; Chen, Xuliang; Fu, Zuli; Shi, Ruizheng; Zhang, Guogang; Xu, Qian; Lin, Guoqiang (Frontiers in Physiology, 2022)
Objective: Oxygenation impairment is a common complication of acute aortic syndrome (AAS) patients after surgical repair. The aim of this study is to identify the relationship between body mass index (BMI) and the risk of postoperative oxygenation impairment in AAS patients. Methods: A total of 227 consecutive patients who were diagnosed as AAS and underwent surgical repair were recruited. They were divided into 2 groups based on the postoperative oxygenation impairment (non-oxygenation impairment group and oxygenation impairment group). Logistic regression was conducted to evaluate the association between BMI and the risk of oxygenation impairment after surgery. Dose-response curve and subgroup analysis were used to test the reliability of the results of regression analysis. Then, a meta-analysis was performed to further confirm the results above using Pubmed, Embase and Web of Science databases. Results: For the retrospective study, a significant association was observed after adjusting for a series of variables. BMI was significantly correlated with postoperative oxygenation impairment in patients with AAS (OR, 95% CI, P: 1.274, 1.0717-1.4346, 0.0014). Compared with the normal weight group (18.5 kg/m2 ≤ BMI < 23.0 kg/m2) group, patients with excessive BMI were at a higher risk of oxygenation impairment for the overweight group (23.0 kg/m2 ≤ BMI < 25 kg/m2) and obesity group (BMI ≥ 25 kg/m2) (OR, 95% CI, P: 5.04.96, 1.623-15.6915, 0.005; 7.079.51, 2.323.06-21.559.57, < 0.001). The dose-response curve showed that the risk of oxygenation impairment after surgery increased with the increased BMI. Besides, subgroup analysis showed that AAS patients have an excess weight with a TNF-α ≥ 8.1pg/ml carried an excess risk of postoperative oxygenation impairment. For the meta-analysis, the pooled result also indicated that AAS patients with high BMI had a significantly increased risk of oxygenation impairment after surgery (OR, 95% CI, P: 1.40, 1.18-1.66, 0.001). Conclusions: Excessive BMI was an independent risk factor for AAS with postoperative oxygenation impairment.